Stocks, bonds and the investment horizon: A spatial dominance approach - Raúl Ibarra-Ramírez (Banco de México, 2011)
Financial advisors typically recommend that a long-term investor should hold a higher percentage of his wealth in stocks than a short-term investor. However, part of the academic literature disagrees with this advice. We use a spatial dominance test which is suited for comparing alternative investments when their distributions are time-varying. Using daily data for the US from 1965 to 2008, we test for dominance of cumulative returns series for stocks versus bonds at different investment horizons from one to ten years. We find that bonds second order spatially dominate stocks for one and two year horizons. For horizons of nine years or longer, we find evidence that stocks dominate bonds. When different portfolios of stocks and bonds are compared, we find that for long investment horizons, only those portfolios with a suffciently high proportion of stocks are effcient in the sense of spatial dominance.
Keywords: C12; C14; G11; 330; Investment decisions; Investment horizon; Stochastic dominance; Kapitalanlage; Portfolio-Management; USA